2023
DOI: 10.3389/fviro.2023.1156012
|View full text |Cite
|
Sign up to set email alerts
|

Co-detection of respiratory syncytial virus with other respiratory viruses across all age groups before and during the COVID-19 pandemic

Abstract: BackgroundPatterns of respiratory syncytial virus (RSV) co-detection with other viruses may have been disrupted during the coronavirus disease 2019 (COVID-19) pandemic, but the clinical impact of viral co-detections with RSV is not well-established. We aimed to explore the frequency and clinical outcomes associated with RSV single detection and co-detection before and during the pandemic.MethodsWe conducted a single-center retrospective cohort study of all children and adults with respiratory samples tested us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…For instance, Agathis and colleagues reported that among children less than 5 years old hospitalized with SARS-CoV-2 infection, co-detection with RSV or RV/EV was significantly associated with severe illness [ 21 ]. Amarin and colleagues observed that for 0- to 4-year-old children, co-detection of RSV with PIV or RV/EV was associated with lower odds of hospitalization and higher odds of intensive care unit admission for RSV-SARS-CoV-2 combination [ 22 ]. A better understanding in this area may facilitate evidence-based prediction of clinical outcomes and improved patient management.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Agathis and colleagues reported that among children less than 5 years old hospitalized with SARS-CoV-2 infection, co-detection with RSV or RV/EV was significantly associated with severe illness [ 21 ]. Amarin and colleagues observed that for 0- to 4-year-old children, co-detection of RSV with PIV or RV/EV was associated with lower odds of hospitalization and higher odds of intensive care unit admission for RSV-SARS-CoV-2 combination [ 22 ]. A better understanding in this area may facilitate evidence-based prediction of clinical outcomes and improved patient management.…”
Section: Discussionmentioning
confidence: 99%